Pequeñas empresas agroindustriales en Tunja - Boyacá, Colombia. Una descripción del cambio organizacional - Acosta-González, Beicy-Viviana; Suarez-Pineda, Marlen; Parada-Camargo, Jenny-Edith (Revista Científica, 2021)
This article presents the results obtained from investigating the organizational change of small companies in the agro-industrial sector of the city of Tunja in the last decade. This research used semi-structured interview techniques and a theoretical review focused on five dimensions: i) organizational change, ii) worker-leaders and managers, iii) government, iv) culture and traditions, and v) failure and resistance. The findings provide companies with a greater understanding of change as a constant and slow process that allows organizations to endure over time. Likewise, the implementation of new technologies has favored the production and growth of organizations.